Phylogenetic relationships in Asphodelaceae (Subfamily Alooideae) inferred from chloroplast DNA sequences (rbcL, matK) and from genomic fingerprinting (ISSR) - Treutlein, Jens; Wink, Michael (Taxon, 2003)
Two independent lines of molecular evidence have been studied to explore phylogenetic relationships in the family Asphodelaceae. Genomic fingerprinting by ISSR (Inter Simple Sequence Repeats) analysis was compared to sequence data of the chloroplast genes matK and rbcL. Molecular data indicate that some long-established taxonomic concepts would have to be re-evaluated. The subfamily Asphodeloideae clusters as a sister group to a distinctly monophyletic Alooideae. However, several Alooideae genera, including Aloe and Haworthia, are apparently not monophyletic. From a molecular point of view, Haworthia can be divided into two distinct groups that agree closely with the current subgeneric classification: a monophyletic group including species of subgenus Haworthia, and a second polyphyletic group with the subgenera Hexangulares and Robustipedunculares. This second clade includes Poellnitzia, Astroloba, Gasteria and even one Haworthia-like aloe (Aloe aristata). In the polyphyletic assemblage currently classified as Aloe, several smaller clades can be recognised, often reflecting morphological, chemical and geographical discontinuities. The tree aloes (sections Aloidendron and Dracoaloe) and climbing aloes (series Macrifoliae) appear to have separated early in Alooideae, while other groups (e.g., the flavonoid-containing group and a Madagascan group) are embedded within and amongst other genera. Chortolirion clusters with the grass-like aloes (section Graminialoe Reynolds, syn. Leptaloe Berger), A. boylei and A. verecunda, on a well-defined branch. The current taxonomic system clearly does not reflect the phylogenetic affinities and relationships amongst the succulent genera Aloe, Astroloba, Chortolirion, Gasteria, Haworthia, and Poellnitzia.